THE OUTPATIENT REGISTRY PROFILE UTILIZATION FOR OBESITY PATIENTS SURVEYING WITH THE AIM OF FOOD RELATED AND EXERCISE RELATED CARDIOVASCULAR RISK ASSESSEMENT - S. Yu. Martsevich; L. P. Ivanova; O. V. Lerman; Yu. V. Lukina; A. V. Zakharova; N. V. Kiseleva (Кардиоваскулярная терапия и профилактика, 2017)
Aim. Under the framework of the outpatient registry PROFILE, to assess cardiovascular risk factors (CVR) related to food and physical activity (PA) in obese patients, using questionnaires.Material and methods. Into the study, obesity patients were included, from PROFILE registry, of those 91 completed survey on food behavior and PA.Results. The prevalence of obesity, by the registry data, was 38,8% (47,3% in women and 52,7% in men). Patients had high and very high CVR by SCORE. Arterial hypertension was found in 85,7%, and the same number had dyslipidemia, coronary heart disease — in 34,1%, glucose intolerance and type 2 diabetes — in 12,1% and 20,9%, respectively, smokers were 16,5%. Most patients had in their food related behavior the adverse factors such as low amount of fruits and vegetables, excess of refined carbohydrates and salt. In 48,4% of patients there was low level of PA. All obesity patients present with a characteristic combination of CVR factors.Conclusion. Surveying of patients under framework of outpatient registry makes it to reveal CVR factors related to food and PA, in real clinical practice.